(3TQM cTa GdCSQGQ ddNhfLis - (3fLe GdOjf Ydj Hf YeQ Hf Ydj GdbRhjfis; (3GdNhfLj , eMeO Hf fGeGhQ Hf YHO Gdedc, GaVd GdOjf CHh YHO Gddg,J (B646 (3g` s ((3eYJhb Hf eSYhO GdSejSGWi s)
(3ChdgG (B:s
(3Gdjg JaUjd eG CLedg hGjQGOg eG Cgedg Ydi hLg Ydi hLg dGJSGb hGdEfJXGe s
(3BNQgG (B:s
(3ai Pdc TQMfG cdGeg hhVMfG eQGeg eY GdMGb eG SfM ddacQ ai GdMGd Edjg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B73s
Keywords: (3GdadSaI hGdefWbs